"Valei-me, são Wittgenstein": poetry and philosophy of the language in Paulo Henriques Britto - Miguel Heitor Braga Vieira (FronteiraZ, 2016)
This article aims at doing an analytical reading of Paulo Henriques Britto´s works starting from an interlocution with the philosophy of language. For this, it uses some conceptual basis set by Ludwig Wittgenstein, especially his ideas about language presented in Tractatus logico-philosophicus and Philosophical Investigations, which, ultimately, reveal a close dialogue between the Brazilian poet and the Austro-British philosopher.